Deriving symmetry of equality in FOL The Next CEO of Stack OverflowNot understanding universal generalisation, and proof that uses itHints and/or help needed for axiomatic deductionHow can universal quantifier manipulation rules be made redundant by the generalization rule (metatheorem)?completeness theorem in Enderton's bookLogical equivalence of a given formulaEquality and its axiomsIs there a finite axiomatization of Tarski's geometry axioms?Why is the rule of substitution of functions an axiom?FOL-Proof that “There is no set of all sets.”A $L$-sentence Deduction using only $L$-sentences.

Why do professional authors make "consistency" mistakes? And how to avoid them?

How long to clear the 'suck zone' of a turbofan after start is initiated?

How to write papers efficiently when English isn't my first language?

How do I go from 300 unfinished/half written blog posts, to published posts?

Robert Sheckley short story about vacation spots being overwhelmed

Why does C# sound extremely flat when saxophone is tuned to G?

What's the point of interval inversion?

Is it okay to store user locations?

How to Reset Passwords on Multiple Websites Easily?

Where to find order of arguments for default functions

Why do remote companies require working in the US?

What do "high sea" and "carry" mean in this sentence?

Whats the best way to handle refactoring a big file?

How do spells that require an ability check vs. the caster's spell save DC work?

How to get regions to plot as graphics

If the heap is initialized for security, then why is the stack uninitialized?

Shade part of a Venn diagram

What makes a siege story/plot interesting?

What can we do to stop prior company from asking us questions?

India just shot down a satellite from the ground. At what altitude range is the resulting debris field?

How do I construct this japanese bowl?

Natural language into sentence logic

What does "Its cash flow is deeply negative" mean?

Describing a person. What needs to be mentioned?



Deriving symmetry of equality in FOL



The Next CEO of Stack OverflowNot understanding universal generalisation, and proof that uses itHints and/or help needed for axiomatic deductionHow can universal quantifier manipulation rules be made redundant by the generalization rule (metatheorem)?completeness theorem in Enderton's bookLogical equivalence of a given formulaEquality and its axiomsIs there a finite axiomatization of Tarski's geometry axioms?Why is the rule of substitution of functions an axiom?FOL-Proof that “There is no set of all sets.”A $L$-sentence Deduction using only $L$-sentences.










1












$begingroup$


In FOL with equality, the axioms of equality are:



  1. $forall x(x=x).$

  2. Let $varphi$ be a formula with free occurences of $x$, and define $varphi'$ by replacing some or all of the free occurences of $x$ in $varphi$ with $y$, then $forall xforall y(x=yrightarrow(varphirightarrowvarphi')).$

The symmetric property of equality becomes a theorem that follows from these, and I've tried the following:


Let $varphiequiv x=x$ and $varphi'equiv y=x$, then by the second schema:
$$forall xforall y(x=yrightarrow(x=xrightarrow y=x)).$$
It's pretty tempting to proceed as follows:
$$forall xforall y(x=yrightarrow(toprightarrow y=x))$$
$$forall xforall y(x=yrightarrow y=x).$$
My doubt however is, is it wrong to assume that the formula $x=x$ is always true, even when all occurences of $x$ are unbound? Does the universal quantification shown in the first axiom make a difference?










share|cite|improve this question









$endgroup$











  • $begingroup$
    Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
    $endgroup$
    – frabala
    Mar 18 at 13:25















1












$begingroup$


In FOL with equality, the axioms of equality are:



  1. $forall x(x=x).$

  2. Let $varphi$ be a formula with free occurences of $x$, and define $varphi'$ by replacing some or all of the free occurences of $x$ in $varphi$ with $y$, then $forall xforall y(x=yrightarrow(varphirightarrowvarphi')).$

The symmetric property of equality becomes a theorem that follows from these, and I've tried the following:


Let $varphiequiv x=x$ and $varphi'equiv y=x$, then by the second schema:
$$forall xforall y(x=yrightarrow(x=xrightarrow y=x)).$$
It's pretty tempting to proceed as follows:
$$forall xforall y(x=yrightarrow(toprightarrow y=x))$$
$$forall xforall y(x=yrightarrow y=x).$$
My doubt however is, is it wrong to assume that the formula $x=x$ is always true, even when all occurences of $x$ are unbound? Does the universal quantification shown in the first axiom make a difference?










share|cite|improve this question









$endgroup$











  • $begingroup$
    Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
    $endgroup$
    – frabala
    Mar 18 at 13:25













1












1








1





$begingroup$


In FOL with equality, the axioms of equality are:



  1. $forall x(x=x).$

  2. Let $varphi$ be a formula with free occurences of $x$, and define $varphi'$ by replacing some or all of the free occurences of $x$ in $varphi$ with $y$, then $forall xforall y(x=yrightarrow(varphirightarrowvarphi')).$

The symmetric property of equality becomes a theorem that follows from these, and I've tried the following:


Let $varphiequiv x=x$ and $varphi'equiv y=x$, then by the second schema:
$$forall xforall y(x=yrightarrow(x=xrightarrow y=x)).$$
It's pretty tempting to proceed as follows:
$$forall xforall y(x=yrightarrow(toprightarrow y=x))$$
$$forall xforall y(x=yrightarrow y=x).$$
My doubt however is, is it wrong to assume that the formula $x=x$ is always true, even when all occurences of $x$ are unbound? Does the universal quantification shown in the first axiom make a difference?










share|cite|improve this question









$endgroup$




In FOL with equality, the axioms of equality are:



  1. $forall x(x=x).$

  2. Let $varphi$ be a formula with free occurences of $x$, and define $varphi'$ by replacing some or all of the free occurences of $x$ in $varphi$ with $y$, then $forall xforall y(x=yrightarrow(varphirightarrowvarphi')).$

The symmetric property of equality becomes a theorem that follows from these, and I've tried the following:


Let $varphiequiv x=x$ and $varphi'equiv y=x$, then by the second schema:
$$forall xforall y(x=yrightarrow(x=xrightarrow y=x)).$$
It's pretty tempting to proceed as follows:
$$forall xforall y(x=yrightarrow(toprightarrow y=x))$$
$$forall xforall y(x=yrightarrow y=x).$$
My doubt however is, is it wrong to assume that the formula $x=x$ is always true, even when all occurences of $x$ are unbound? Does the universal quantification shown in the first axiom make a difference?







first-order-logic predicate-logic






share|cite|improve this question













share|cite|improve this question











share|cite|improve this question




share|cite|improve this question










asked Mar 18 at 13:03









mjtsquaredmjtsquared

12715




12715











  • $begingroup$
    Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
    $endgroup$
    – frabala
    Mar 18 at 13:25
















  • $begingroup$
    Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
    $endgroup$
    – frabala
    Mar 18 at 13:25















$begingroup$
Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
$endgroup$
– frabala
Mar 18 at 13:25




$begingroup$
Your approach shows only that equality is symmetric over variables. What you want to show is that if $phi = phi'$ then $phi' = phi$. For that, you have to use part (2) of the definition.
$endgroup$
– frabala
Mar 18 at 13:25










1 Answer
1






active

oldest

votes


















1












$begingroup$


is it wrong to assume [in the proof of simmetry of equality] that the formula $x=x$ is always true?




No, it works.



More detailed proof :



1) $vdash forall x (x=x)$ --- axiom 1



2) $vdash ∀x∀y(x=y → (x=x → y=x))$ --- from axiom-schema 2 : $∀x∀y(x=y → (phi[z/x] → phi[z/y]))$, where $phi(z) := (z=x)$



3) $x=y$ --- assumed [a]



4) $x=x$ --- from 1) by $forall$-elim (i.e. Universal Instantiation)



5) $x=y → (x=x → y=x)$ --- from 2) by $forall$-elim



6) $(x=x → y=x)$ --- from 3) and 5) by $to$-elim (aka Modus Ponens)



7) $y=x$ --- from 4) and 6)



8) $(x=y to y=x)$ --- from 3) and 7) by $to$-intro (aka Conditional Proof), discharging [a]




$vdash ∀x∀y(x=y to y=x)$ --- from 8) by $forall$-intro (i.e. Universal generalization) twice.







share|cite|improve this answer











$endgroup$













    Your Answer





    StackExchange.ifUsing("editor", function ()
    return StackExchange.using("mathjaxEditing", function ()
    StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix)
    StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
    );
    );
    , "mathjax-editing");

    StackExchange.ready(function()
    var channelOptions =
    tags: "".split(" "),
    id: "69"
    ;
    initTagRenderer("".split(" "), "".split(" "), channelOptions);

    StackExchange.using("externalEditor", function()
    // Have to fire editor after snippets, if snippets enabled
    if (StackExchange.settings.snippets.snippetsEnabled)
    StackExchange.using("snippets", function()
    createEditor();
    );

    else
    createEditor();

    );

    function createEditor()
    StackExchange.prepareEditor(
    heartbeatType: 'answer',
    autoActivateHeartbeat: false,
    convertImagesToLinks: true,
    noModals: true,
    showLowRepImageUploadWarning: true,
    reputationToPostImages: 10,
    bindNavPrevention: true,
    postfix: "",
    imageUploader:
    brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
    contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
    allowUrls: true
    ,
    noCode: true, onDemand: true,
    discardSelector: ".discard-answer"
    ,immediatelyShowMarkdownHelp:true
    );



    );













    draft saved

    draft discarded


















    StackExchange.ready(
    function ()
    StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3152758%2fderiving-symmetry-of-equality-in-fol%23new-answer', 'question_page');

    );

    Post as a guest















    Required, but never shown

























    1 Answer
    1






    active

    oldest

    votes








    1 Answer
    1






    active

    oldest

    votes









    active

    oldest

    votes






    active

    oldest

    votes









    1












    $begingroup$


    is it wrong to assume [in the proof of simmetry of equality] that the formula $x=x$ is always true?




    No, it works.



    More detailed proof :



    1) $vdash forall x (x=x)$ --- axiom 1



    2) $vdash ∀x∀y(x=y → (x=x → y=x))$ --- from axiom-schema 2 : $∀x∀y(x=y → (phi[z/x] → phi[z/y]))$, where $phi(z) := (z=x)$



    3) $x=y$ --- assumed [a]



    4) $x=x$ --- from 1) by $forall$-elim (i.e. Universal Instantiation)



    5) $x=y → (x=x → y=x)$ --- from 2) by $forall$-elim



    6) $(x=x → y=x)$ --- from 3) and 5) by $to$-elim (aka Modus Ponens)



    7) $y=x$ --- from 4) and 6)



    8) $(x=y to y=x)$ --- from 3) and 7) by $to$-intro (aka Conditional Proof), discharging [a]




    $vdash ∀x∀y(x=y to y=x)$ --- from 8) by $forall$-intro (i.e. Universal generalization) twice.







    share|cite|improve this answer











    $endgroup$

















      1












      $begingroup$


      is it wrong to assume [in the proof of simmetry of equality] that the formula $x=x$ is always true?




      No, it works.



      More detailed proof :



      1) $vdash forall x (x=x)$ --- axiom 1



      2) $vdash ∀x∀y(x=y → (x=x → y=x))$ --- from axiom-schema 2 : $∀x∀y(x=y → (phi[z/x] → phi[z/y]))$, where $phi(z) := (z=x)$



      3) $x=y$ --- assumed [a]



      4) $x=x$ --- from 1) by $forall$-elim (i.e. Universal Instantiation)



      5) $x=y → (x=x → y=x)$ --- from 2) by $forall$-elim



      6) $(x=x → y=x)$ --- from 3) and 5) by $to$-elim (aka Modus Ponens)



      7) $y=x$ --- from 4) and 6)



      8) $(x=y to y=x)$ --- from 3) and 7) by $to$-intro (aka Conditional Proof), discharging [a]




      $vdash ∀x∀y(x=y to y=x)$ --- from 8) by $forall$-intro (i.e. Universal generalization) twice.







      share|cite|improve this answer











      $endgroup$















        1












        1








        1





        $begingroup$


        is it wrong to assume [in the proof of simmetry of equality] that the formula $x=x$ is always true?




        No, it works.



        More detailed proof :



        1) $vdash forall x (x=x)$ --- axiom 1



        2) $vdash ∀x∀y(x=y → (x=x → y=x))$ --- from axiom-schema 2 : $∀x∀y(x=y → (phi[z/x] → phi[z/y]))$, where $phi(z) := (z=x)$



        3) $x=y$ --- assumed [a]



        4) $x=x$ --- from 1) by $forall$-elim (i.e. Universal Instantiation)



        5) $x=y → (x=x → y=x)$ --- from 2) by $forall$-elim



        6) $(x=x → y=x)$ --- from 3) and 5) by $to$-elim (aka Modus Ponens)



        7) $y=x$ --- from 4) and 6)



        8) $(x=y to y=x)$ --- from 3) and 7) by $to$-intro (aka Conditional Proof), discharging [a]




        $vdash ∀x∀y(x=y to y=x)$ --- from 8) by $forall$-intro (i.e. Universal generalization) twice.







        share|cite|improve this answer











        $endgroup$




        is it wrong to assume [in the proof of simmetry of equality] that the formula $x=x$ is always true?




        No, it works.



        More detailed proof :



        1) $vdash forall x (x=x)$ --- axiom 1



        2) $vdash ∀x∀y(x=y → (x=x → y=x))$ --- from axiom-schema 2 : $∀x∀y(x=y → (phi[z/x] → phi[z/y]))$, where $phi(z) := (z=x)$



        3) $x=y$ --- assumed [a]



        4) $x=x$ --- from 1) by $forall$-elim (i.e. Universal Instantiation)



        5) $x=y → (x=x → y=x)$ --- from 2) by $forall$-elim



        6) $(x=x → y=x)$ --- from 3) and 5) by $to$-elim (aka Modus Ponens)



        7) $y=x$ --- from 4) and 6)



        8) $(x=y to y=x)$ --- from 3) and 7) by $to$-intro (aka Conditional Proof), discharging [a]




        $vdash ∀x∀y(x=y to y=x)$ --- from 8) by $forall$-intro (i.e. Universal generalization) twice.








        share|cite|improve this answer














        share|cite|improve this answer



        share|cite|improve this answer








        edited Mar 25 at 11:34

























        answered Mar 18 at 13:26









        Mauro ALLEGRANZAMauro ALLEGRANZA

        67.5k449117




        67.5k449117



























            draft saved

            draft discarded
















































            Thanks for contributing an answer to Mathematics Stack Exchange!


            • Please be sure to answer the question. Provide details and share your research!

            But avoid


            • Asking for help, clarification, or responding to other answers.

            • Making statements based on opinion; back them up with references or personal experience.

            Use MathJax to format equations. MathJax reference.


            To learn more, see our tips on writing great answers.




            draft saved


            draft discarded














            StackExchange.ready(
            function ()
            StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3152758%2fderiving-symmetry-of-equality-in-fol%23new-answer', 'question_page');

            );

            Post as a guest















            Required, but never shown





















































            Required, but never shown














            Required, but never shown












            Required, but never shown







            Required, but never shown

































            Required, but never shown














            Required, but never shown












            Required, but never shown







            Required, but never shown







            Popular posts from this blog

            Solar Wings Breeze Design and development Specifications (Breeze) References Navigation menu1368-485X"Hang glider: Breeze (Solar Wings)"e

            Kathakali Contents Etymology and nomenclature History Repertoire Songs and musical instruments Traditional plays Styles: Sampradayam Training centers and awards Relationship to other dance forms See also Notes References External links Navigation menueThe Illustrated Encyclopedia of Hinduism: A-MSouth Asian Folklore: An EncyclopediaRoutledge International Encyclopedia of Women: Global Women's Issues and KnowledgeKathakali Dance-drama: Where Gods and Demons Come to PlayKathakali Dance-drama: Where Gods and Demons Come to PlayKathakali Dance-drama: Where Gods and Demons Come to Play10.1353/atj.2005.0004The Illustrated Encyclopedia of Hinduism: A-MEncyclopedia of HinduismKathakali Dance-drama: Where Gods and Demons Come to PlaySonic Liturgy: Ritual and Music in Hindu Tradition"The Mirror of Gesture"Kathakali Dance-drama: Where Gods and Demons Come to Play"Kathakali"Indian Theatre: Traditions of PerformanceIndian Theatre: Traditions of PerformanceIndian Theatre: Traditions of PerformanceIndian Theatre: Traditions of PerformanceMedieval Indian Literature: An AnthologyThe Oxford Companion to Indian TheatreSouth Asian Folklore: An Encyclopedia : Afghanistan, Bangladesh, India, Nepal, Pakistan, Sri LankaThe Rise of Performance Studies: Rethinking Richard Schechner's Broad SpectrumIndian Theatre: Traditions of PerformanceModern Asian Theatre and Performance 1900-2000Critical Theory and PerformanceBetween Theater and AnthropologyKathakali603847011Indian Theatre: Traditions of PerformanceIndian Theatre: Traditions of PerformanceIndian Theatre: Traditions of PerformanceBetween Theater and AnthropologyBetween Theater and AnthropologyNambeesan Smaraka AwardsArchivedThe Cambridge Guide to TheatreRoutledge International Encyclopedia of Women: Global Women's Issues and KnowledgeThe Garland Encyclopedia of World Music: South Asia : the Indian subcontinentThe Ethos of Noh: Actors and Their Art10.2307/1145740By Means of Performance: Intercultural Studies of Theatre and Ritual10.1017/s204912550000100xReconceiving the Renaissance: A Critical ReaderPerformance TheoryListening to Theatre: The Aural Dimension of Beijing Opera10.2307/1146013Kathakali: The Art of the Non-WorldlyOn KathakaliKathakali, the dance theatreThe Kathakali Complex: Performance & StructureKathakali Dance-Drama: Where Gods and Demons Come to Play10.1093/obo/9780195399318-0071Drama and Ritual of Early Hinduism"In the Shadow of Hollywood Orientalism: Authentic East Indian Dancing"10.1080/08949460490274013Sanskrit Play Production in Ancient IndiaIndian Music: History and StructureBharata, the Nāṭyaśāstra233639306Table of Contents2238067286469807Dance In Indian Painting10.2307/32047833204783Kathakali Dance-Theatre: A Visual Narrative of Sacred Indian MimeIndian Classical Dance: The Renaissance and BeyondKathakali: an indigenous art-form of Keralaeee

            Method to test if a number is a perfect power? Announcing the arrival of Valued Associate #679: Cesar Manara Planned maintenance scheduled April 23, 2019 at 00:00UTC (8:00pm US/Eastern)Detecting perfect squares faster than by extracting square rooteffective way to get the integer sequence A181392 from oeisA rarely mentioned fact about perfect powersHow many numbers such $n$ are there that $n<100,lfloorsqrtn rfloor mid n$Check perfect squareness by modulo division against multiple basesFor what pair of integers $(a,b)$ is $3^a + 7^b$ a perfect square.Do there exist any positive integers $n$ such that $lfloore^nrfloor$ is a perfect power? What is the probability that one exists?finding perfect power factors of an integerProve that the sequence contains a perfect square for any natural number $m $ in the domain of $f$ .Counting Perfect Powers